1981
DOI: 10.2136/sssaj1981.03615995004500060045x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Water Content by Microwave Drying: A Routing Procedure

Abstract: A routine procedure was established for determining soil water content by microwave drying. The procedure requires small, 20‐gram soil samples heated for a 20‐min period at full power (600 to 650 W) in a household‐type microwave oven. Using this procedure, consistent agreement (within 0.5 wt%) was obtained between microwave and electric oven drying for soil materials ranging from quartz sands to fine silts and clays, with water contents ranging from air‐dry to saturation and with organic matter ranging from 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…The results indicated that a 20 rain drying time for four soil samples (50-60 g each) in a microwave oven provided average soil water content values within i% of those obtained.in a conventional oven for all soil types and soil water levels. These data are comparable with the 20 min drying for samples of 20 g using a maximum power setting (600-650 W) obtained by Gee and Dodson (1981). Soil water content of the air dry samples (i.e., low level of soil water content) could be determined with a 12 rain drying time for all soil types, but increasing the drying time did not affect the accuracy of results.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The results indicated that a 20 rain drying time for four soil samples (50-60 g each) in a microwave oven provided average soil water content values within i% of those obtained.in a conventional oven for all soil types and soil water levels. These data are comparable with the 20 min drying for samples of 20 g using a maximum power setting (600-650 W) obtained by Gee and Dodson (1981). Soil water content of the air dry samples (i.e., low level of soil water content) could be determined with a 12 rain drying time for all soil types, but increasing the drying time did not affect the accuracy of results.…”
Section: Resultssupporting
confidence: 80%
“…The successful use of a microwave oven for rapid soil water content determination has also been reported (Miller et al 1974;Hankin and Sawhney 1978;Gee and Dodson 1981). Soil drying using a microwave oven can be achieved in minutes rather than hours.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…A routine procedure was established for determining the soil water content by microwave drying. The procedure requires small (20‐g) soil samples, which are heated for 20 min at full power (600–650 W) in a household‐type microwave oven (Gee and Dodson, 1981). The water content at field capacity (–0.33 kPa) was 28% and at the permanent wilting point (–1500 kPa) was 14.5% determined with a pressure plate.…”
Section: Methodsmentioning
confidence: 99%
“…We determined moisture content of a subsample of each of the 20 samples by microwave drying (Gee and Dodson, 1981). Each sample was sieved through a 2 mm sieve in the field moist state and kept at 5°C in plastic containers.…”
Section: Laboratory Soil Respiration and Residue Decompositionmentioning
confidence: 99%